Shierry Weber Nicholsen: The Love of Nature and the End of the World. The Unspoken Dimension of Enviromental Concern. The MIT Press, Cambridge, Massachusetts, 2002 - Gonzalo, Enrique (Foro Interno, 2002)
Sin resumen